Abolishment of a tax on imputed income: consequences for business and budget - N. Z. Zotikov (Вестник университета, 2023)
The article purpose is to investigate changes of taxpayers in the simplified and patent taxation system, in the structure of tax revenues of regional and local budgets, in the tax burden on taxpayers that occurred in connection with the abolition of tax on imputed income (from 2021). The research used generally accepted methods of scientific cognition, such as analysis, synthesis, generalization, grouping, tabular method. The information base of the study was the Tax Code of the Russian Federation, official reporting data of the Federal Tax Service of Russian Federation, authors’ publications on the topic under study. The study obtained the following results. The tax revenues of local budgets decreased, having lost the source of income in the form of tax on imputed income, previously credited in full; the tax burden on taxpayers increased (when tax on imputed income was applied, it was minimal). The main conclusion of the study is the fact that the patent taxation system, which can be applied by entrepreneurs who have ceased to be payers of tax on imputed income, needs a radical transformation. It is necessary to improve the efficiency of such system in terms of determining the amount of income from which the cost of a patent is calculated.